Spiritual Dimension and Contemporary Fiqh Perspective in Parents' Fasting Practices for Children's Success - Umam, Rizal Khoirul; Hamidah, Tutik (Civiliza Publishing, 2023)
Fasting in Islam not only demands physical obedience, but also includes spiritual, social and educational dimensions. Apart from being a means of increasing piety, fasting strengthens social awareness and togetherness, both within families and communities. The tradition of parents fasting to pray for their children's success demonstrates the role of this act of worship in supporting spiritual education. However, from a classical fiqh perspective, the intention of fasting should be purely to seek Allah's pleasure, not for worldly purposes. Meanwhile, contemporary scholars emphasize the importance of maintaining a balance between the intention of worship and the reality of life, so that the spiritual essence of fasting is maintained. The research method used is descriptive qualitative with the type of Library Research to understand and examine fasting for children's success from the perspective of contemporary fiqh. The results of this study indicate the importance of maintaining the intention of fasting for the sake of Allah SWT without any intention other than Allah. Contemporary jurisprudence offers a solution by allowing parents to fast with the intention of being sincere to Allah, while increasing other worship such as prayer and almsgiving whose rewards are intended for the success of the child. This approach allows parents to support their children's success spiritually without compromising the virtue of fasting itself.